Design and high order optimization of the Accelerator Test Facility lattices - Marin, E; Tomas, R; Bambade, P; Kubo, K; Okugi, T; Tauchi, T; Terunuma, N; Urakawa, J; Seryi, A; White, G; Woodley, M (2014)
The Accelerator Test Facility 2 (ATF2) aims to test the novel chromaticity correction scheme which is implemented in the final focus systems of future linear colliders such as the International Linear Collider (ILC) and the Compact Linear Collider (CLIC). The ATF2 nominal and ultralow β* lattices are designed to vertically focus the beam at the focal point, or usually referred to as interaction point (IP), down to 37 and 23 nm, respectively. The vertical chromaticities of the nominal and ultralow β* lattices are comparable to those of ILC and CLIC, respectively. When the measured multipole components of the ATF2 magnets are considered in the simulations, the evaluated spot sizes at the IP are well above the design values. In this paper we describe the analysis of the high order aberrations that allows identifying the sources of the observed beam size growth. In order to recover the design spot sizes three solutions are considered, namely final doublet replacement, octupole insertion, and optics modification. Concerning the future linear collider projects, the consequences of magnetic field errors of the focusing quadrupole magnet of the final doublet are also addressed. © Published by the American Physical Society.